Validity and Reliability of a Commercially Available Indoor Tracking System to Assess Distance and Time in Court-Based Sports - Colino, Enrique; Garcia-Unanue, Jorge; Sanchez-Sanchez, Javier; Calvo-Monera, Javier; Leon, Manuel; Carvalho, María Jose; Gallardo, Leonor; Felipe, Jose Luis; Navandar, Archit (Frontiers in Psychology, 2019)
The aim of this study was to evaluate the validity and reliability of a commercially available Local Position Measurement (LPM) tracking system when assessing distance and running time at different speeds. Fifteen male healthy athletes performed 15-meter displacements at walking, running and sprinting speed. Data recorded by the LPM system were compared to those from the reference equipment, consisting of measuring tape and electronic timing gates placed at 0, 5, 10 and 15 m. Mean error, mean absolute error, SD of the measurement error, maximum measurement error and root mean square error were calculated to determine the validity for distance and the running time variables. Product-moment correlation and intraclass correlation coefficient were also used for the running time. Finally, the reliability of the distance was carried out comparing data from the three repetitions with the standard tape measure using a linear mixed model and the typical error as mean coefficient of variation (%). Mean absolute error show errors under 0.18 m for the distance variable at all speeds and under 0.08 for the running time variable at all speeds, except from 15 m at walking. Product-Moment Correlations were high to nearly perfect for running time (range: 0.60-0.99), intraclass correlation coefficient varied between high (0.75-0.90) and extremely high (>0.99) for most measures, and coefficients of variation remained almost invariable as speed increased (walking: 2.16; running: 2.52; sprinting: 2.20). The tested LPM system represents a valid and reliable method for monitoring distance during different constant speeds over a straight line. However, the running time errors could be too large for performance tests that require acute precision.